Aprendizagem organizacional em empreendimentos contemplados por um programa de incubação - Carletti, Raquel Menezes (2018)
The purpose of this research was to comprehend and analyze the organizational learning (OL) processes enacted throughout the development of new ventures assigned to a business incubation program. The analysis was contextualized from the concepts and discussions about OL and it was based on the 4I model proposed by Crossan et al. (1999), which understands OL as a multilevel and situated phenomenon, within a process orientation and that integrates cognitive, psychological and social aspects. Concerning a qualitative exploratory-descriptive approach, a case study was accomplished in a national prominent business incubator located in Greater Florianópolis (SC), considering the development of five of its incubated and graduated enterprises (incorporated cases). Data were collected from interviews with entrepreneurs, documents and unsystematic observations. The thematic narrative analysis (RIESSMAN, 2008) was applied as the methodological choice to evaluate the results. The use of the 4I model helped to recognize learning as a dynamic process, operating at multiple levels throughout the development of new enterprises inserted in the incubation program. From observations, it was suggested that learning at organizational level in incubated enterprises develops in cycles of intensification and stabilization according to specific events (such as the formal foundation of the company, the elaboration of the business plan, the joint with an capital venture and the expansion of the staff), side by side with the intensification of learning at individual and at group levels. Throughout the entrepreneurial stories, elements and experiences mobilized for the learning of entrepreneurs and work groups ⎯ such as interaction and collaboration, experiencing, the observation of models and the feedback from clients⎯ have been identified and highlighted, reinforcing the idea that learning enacts in social relations and is closely linked to the empirical experience of the entrepreneurs. Findings brought to light the interdependence between the entrepreneur’s individual learning and their enterprise’s OL, the relevance of group learning processes in the context of entrepreneurship and the role of the networking for the OL of incubated ventures. The present study has contributed to bring together two fields of scholarly inquiry ⎯ entrepreneurship and OL ⎯ and to address some gaps pointed in the Brazilian literature of the latter, such as the analysis of the phenomenon from a multilevel approach and its empirical observation in contexts of small organizations. As guidelines for future research, it is suggested to deeply investigate the interorganizational learning in the context of business incubation by incorporating other actors from the entrepreneurship networking and to inquiry on the role of reflection on new venture OL process by conducting longitudinal studies.